Wind direction azimuthal signature in the stokes emission vector from the ocean surface at microwave frequencies - Camps. A. J., author; Reising, S. C., author; John Wiley & Sons, Inc., publisher (Colorado State University. Libraries, 2001)
An ocean polarimetric emission model is presented. It is found that skewness and upwind/cross-wind rms slopes are responsible for the first and second azimuthal harmonic, respectively. Atmospheric effects contribute significantly at low wind speeds, and at horizontal polarization at certain observation angles. Simulation results compare favorably with reported JPL-WINDRAD measurements.